Effect of scapular upward rotation exercises on scapular neuromuscular tenderness in subjects with depressed scapular alignment - Al-Afify, Doha H.; Kamel, Ragia; Shalaby, Amr S. (International journal of health sciences, 2022)
Among the numerous scapular mal-alignments, scapular downward rotation (SDR) presents with depression, abduction and scapular tilt, attributed to upper trapezius elongation and levator scapulae stiffness, which consequently impacts scapular upward rotation. Scapular upward rotation exercise (SURE) that increase scapular upward rotators’ strength and stretch scapular downward rotator, provide the SDR patient with optimum muscle conditions in terms length and strength. This study was carried out to investigate the impact of upward rotation exercises on scapular muscles tenderness in subjects with scapular downward rotation alignment. Setting the p value at p < 0.001, the six weeks of intervention significantly improved pressure pain threshold (PPT) post-treatment of median, ulnar, radial nerves, upper trapezius, and upper and lower cervical facet joints (C2/C3 and C5/C6 zygapophyseal joints) compared to those of pre-treatment, with a percent of increase  of 81.85%, 93.38%, 92.68%, 87.54%, 76.32% and 69.66 % respectively. These results suggest that scapular upward rotation exercises regain optimal scapular function and posture that reduces neuromuscular tenderness in subjects with SDR.